A new bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea) from Northwest Africa with comparative remarks on the subgenus Microdasypoda Michez - Radchenko, Vladimir G.; Ghisbain, Guillaume; Michez, Denis (Zootaxa, 2022)
North Africa, with its vast array of ecosystems and reliefs, constitutes a remarkable place to explore and describe the diversity of wild bees. In this paper, a new bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea, Melittidae), D. schwarzi Radchenko et Michez sp. nov., is described from the Atlas Mountains area (Morocco and Tunisia). This species belongs to the subgenus Microdasypoda Michez and is phenotypically related to D. brevicornis Pérez, but differs from all other species of this subgenus by the structure of the male genitals, the metasomal sterna, and by its overall hair colour. A detailed comparative diagnosis of D. schwarzi with the other four species of this subgenus is provided, as well as a key to the males of Microdasypoda, and a correction to the diagnosis of the subgenus. This new species is the fortieth described Dasypoda species and should be looked for in other mountain regions of Northwest Africa, such as in the Algerian Atlas where it could be present.